2011
DOI: 10.1089/ten.tea.2010.0526
|View full text |Cite
|
Sign up to set email alerts
|

Elastogenic Inductability of Smooth Muscle Cells from a Rat Model of Late Stage Abdominal Aortic Aneurysms

Abstract: Although abdominal aortic aneurysms (AAA) can be potentially stabilized by inhibiting inflammatory cell recruitment and their release of proteolytic enzymes, active AAA regression is not possible without regeneration of new elastic matrix structures. Unfortunately, postneonatal vascular smooth muscle cells (SMCs), healthy, and likely more so, diseased cells, poorly synthesize or remodel elastic fibers, impeding any effort directed at regenerative AAA treatment. Previously, we determined the eleastogenic benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 36 publications
7
62
0
Order By: Relevance
“…It is also apparent from our results that similar to our recently published observations in 2D cultures, TGF-b1 effects dominate with a biphasic dose-dependent proliferative response to TGF-b1 at both HA-o doses. 32 However, from the standpoint of a tissue engineering application, wherein growth in tissue mass is contingent on increased availability of ECM-generating cells, the HA-o/TGF-b1 dose combination that provides greater impetus to SMC proliferation (i.e., 0.1 ng/mL of TGF-b1 and 0.2 or 2 mg/mL of HA-o) is most desirable.…”
mentioning
confidence: 99%
“…It is also apparent from our results that similar to our recently published observations in 2D cultures, TGF-b1 effects dominate with a biphasic dose-dependent proliferative response to TGF-b1 at both HA-o doses. 32 However, from the standpoint of a tissue engineering application, wherein growth in tissue mass is contingent on increased availability of ECM-generating cells, the HA-o/TGF-b1 dose combination that provides greater impetus to SMC proliferation (i.e., 0.1 ng/mL of TGF-b1 and 0.2 or 2 mg/mL of HA-o) is most desirable.…”
mentioning
confidence: 99%
“…Unlike collagen fibers, which undergo natural regenerative repair postdisruption, elastic fibers are poorly restored, due to poor elastogenesis, and impaired elastic fiber assembly by postneonatal and diseased vascular SMCs. 6,7,29,30 Thus, to achieve AAA growth arrest, elastin regeneration must significantly exceed its breakdown. 31 Previously, 10 we showed that BM-SMCs exhibit high elastogenesis and generate paracrine secretions that stimulate elastogenesis by EaRASMCs, findings which support their use for matrix regenerative AAA therapy, provided they can be efficiently delivered to the AAA wall.…”
Section: Discussionmentioning
confidence: 99%
“…6 Similarly, control healthy rat aortic SMCs (RASMCs) were isolated from healthy adult rats (n = 3). 6 The primary cells were cultured for 2 weeks in Dulbecco's modified Eagle's medium-F12 (Invitrogen) supplemented with 10% v/v fetal bovine serum (FBS; Invitrogen) and 1% v/v penicillin-streptomycin (Penstrep; Thermo Fisher) and passaged before use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations